Structural Diversity of Trichomes and its Taxonomic Implications in Tribe Cercideae Bronn of Family Fabaceae - Joshi, Sangeeta; Rawat, Dharmendra Singh; Verma, Smriti Raj (Indian Forester, 2023)
Vestiture and trichomes are easily observable micro-morphological features present in flowering plants. Vestiture types and trichome micro-morphology of six species belonging to genus Bauhinia L. (s.s.) and Phenera Lour. of tribe Cercideae Bronn was studied using light microscope. The purpose of this study is to examine vestiture type and trichome morphology of these taxa and use of this information in taxonomy. A total of 128 surfaces of vegetative and reproductive parts of these species were observed out of which 80 (68.75%) bear trichomes and 40 (31.25%) were glabrous. Eleven different vestiture types on different plant surfaces (vegetative as well as reproductive parts) were recorded. Key developed here based on vestiture types on vegetative plant parts is useful in differentiating species. Structural diversity of trichome in these species is high with 22 different types of trichomes recorded. Bauhinia displays higher diversity of trichomes with 19 types (4 glandular, 15 non-glandular) while Phanera bear 4 types (2 glandular, 2 non-glandular) only. Key developed using characters of trichomes present on vegetative surfaces can be used in differentiating all studied species. A comparison of vestiture and trichome characters between Bauhinia and Phanera agree with the current separation of these two genera.